A variational mode decomposition based approach for cardiopulmonary resuscitation estimation and assessment - Tran, Thi-Thao; Pham, Van-Truong (Vietnam Journal of Science and Technology, 2019)
Cardiac arrests remain leading causes of deaths for thousands of people annually. One of the most common methods for cardiac arrest treatment is cardiopulmonary resuscitation (CPR) that provides chest compressions. It has been shown that the quality of chest compression is considered as one of key indicators for assessment of CPR performance. In this paper, we present an approach for CPR quality evaluation using ECG contaminated with CPR artifact and thoracic impedance. The proposed approach contains two key steps: First, the CPR artifact signal is estimated via variational mode decomposition (VMD) and a mode selection algorithm based on mode’s frequency and frequency of thoracic impedance signal. In the second step, CPR parameters performed on the estimated CPR signals are computed and compared with those derived by reference CPR. The proposed approach is applied for a dataset including patients presenting with asystole, ventricular tachycardia, and pulseless electrical activity. Quantitative results validate the performance of the proposed approach for CPR quality assessment.